2022
DOI: 10.7759/cureus.23249
|View full text |Cite
|
Sign up to set email alerts
|

Encephalocele: A Case Series From Abuja, North Central Nigeria

Abstract: An encephalocele is a congenital tube defect in which there is an extension of intracranial structures outside the normal confines of the skull. Its presentation at birth provokes a lot of anxiety amongst parents, guardians and care providers with regards to compatibility with life, surgical treatments and effects on developmental milestones and higher mental functions. This report is on our initial experience in the first six months following surgical treatment of four consecutive cases presenting in infancy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Experiences in other parts of Nigeria and Africa seem to support this view. A study in Abuja, Nigeria, [34] reported that across a 4-year period, 57 patients presented with aSAH but only 25 were confirmed to harbor 27 aneurysms while 47% could not afford the cost of confirmation investigations, thus giving an annual A recent scoping review of aneurysmal SAH in Africa revealed the scanty publications on this important subject that dominates neurosurgical literature. [30] Interestingly, most of the publications emanated from North African countries.…”
Section: Does the Study Suggest Low Frequency Of Aneurysms In Enugu?mentioning
confidence: 99%
See 3 more Smart Citations
“…Experiences in other parts of Nigeria and Africa seem to support this view. A study in Abuja, Nigeria, [34] reported that across a 4-year period, 57 patients presented with aSAH but only 25 were confirmed to harbor 27 aneurysms while 47% could not afford the cost of confirmation investigations, thus giving an annual A recent scoping review of aneurysmal SAH in Africa revealed the scanty publications on this important subject that dominates neurosurgical literature. [30] Interestingly, most of the publications emanated from North African countries.…”
Section: Does the Study Suggest Low Frequency Of Aneurysms In Enugu?mentioning
confidence: 99%
“…Autopsy studies have provided information on the incidence of IAs although there may be concerns about the accuracy [29] Ibadan Nigeria 1988-1999 17 1.6 Ohaegbulam [24] Enugu, Nigeria 1974-1977 5 1.7 Ugwuanyi et al [34] Abuja Nigeria 2016-2020 27 6.7 Tokpa et al [33] Abidjan Corte Ivoire 2012-2018 128 18.3 ioub et al [32] Dakar Senegal 2013-2016 129 36.8 Ogenga' o et al [22] Nairobi Kenya 1998-2007 56 6.2 Nabaweesi-Batuka et al [19] Nairobi, Kenya 2010-2014 121 30 El Khamlichi et al [5] Rabat Morocco 1983-1999 200 11.7 Khan et al [12] Quarter 2007-2016 323 32.3 Ramnarayan et al [26] Kozhikode, India 1998-2003 182 36.4 Law et al [16] Hong Kong 2002-2006 135 33.75 van Munster et al [35] Kuopulo Finland 1986-2005 1786 94 van Munster et al [35] Utrecht, Netherlands 1986-2005 1788 94 Korja et al [14] Helsinki, Finland 1995-2009 1993 142.4…”
Section: Does the Study Suggest Low Frequency Of Aneurysms In Enugu?mentioning
confidence: 99%
See 2 more Smart Citations
“…Bu kusurlar beyni, omurgayı veya omuriliği etkileyebilir ve genellikle hamileliğin ilk ayında ortaya çıkar. Kusurlu embriyogenez dışında, viral enfeksiyon, hipertermi, radyasyon, hipervitaminoz, hipoksi ve erken gebelikte salisilat tedavisi gibi çeşitli faktörler oluşumuna katkıda bulunabilir (2,3). Kranial disrafizm, kraniyal nöral tüpün kapanmaması durumudur ve anensefali ve ensefalosel içerir.…”
Section: Introductionunclassified